2021
DOI: 10.1126/sciadv.abd5684
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic pacing of medial septum parvalbumin-positive cells disrupts temporal but not spatial firing in grid cells

Abstract: Grid cells in the medial entorhinal cortex (MEC) exhibit remarkable spatial activity patterns with spikes coordinated by theta oscillations driven by the medial septal area (MSA). Spikes from grid cells progress relative to the theta phase in a phenomenon called phase precession, which is suggested as essential to create the spatial periodicity of grid cells. Here, we show that optogenetic activation of parvalbumin-positive (PV+) cells in the MSA enabled selective pacing of local field potential (LFP) oscillat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 83 publications
(119 reference statements)
5
19
0
Order By: Relevance
“…Previous research has shown that inactivation of the MSA and subsequent reduction of theta amplitude has a selective effect on reducing the spatial firing of grid cells while other hippocampal and mEC cell types remain intact 25 , 26 . Interestingly, our results and a recently published study 47 do not show any substantial alterations to grid or head-direction coding in mEC when manipulating the timing of septal oscillations. In contrast to the lack of effects with septal pacing, previous studies with pharmacological inactivation of the MSA caused a large reduction of not only theta oscillations, but also of firing rates of principal cells in the entorhino-hippocampal circuit 25 , 26 , 48 .…”
Section: Discussionsupporting
confidence: 53%
“…Previous research has shown that inactivation of the MSA and subsequent reduction of theta amplitude has a selective effect on reducing the spatial firing of grid cells while other hippocampal and mEC cell types remain intact 25 , 26 . Interestingly, our results and a recently published study 47 do not show any substantial alterations to grid or head-direction coding in mEC when manipulating the timing of septal oscillations. In contrast to the lack of effects with septal pacing, previous studies with pharmacological inactivation of the MSA caused a large reduction of not only theta oscillations, but also of firing rates of principal cells in the entorhino-hippocampal circuit 25 , 26 , 48 .…”
Section: Discussionsupporting
confidence: 53%
“…Although it was reported that time (but not place) cells could depend directly on the medial entorhinal cortex (MEC) inputs 61 , recent experimental evidence suggests that MEC lesions do not lead to any alterations in hippocampal time cell physiology 62 . Notably, a more recent investigation found that optogenetic pacing of the MS did not disrupt the spatial codes of grid cells in the entorhinal cortex 63 , further suggesting that MS activity is not directly involved in spatial codes within the hippocampal formation. Together with our results, this indicates that temporal codes could either be the result of MS-dependent computations within the entorhinal cortex 63 (1) or be generated intrinsically within the hippocampus itself (2).…”
Section: Discussionmentioning
confidence: 96%
“…Notably, a more recent investigation found that optogenetic pacing of the MS did not disrupt the spatial codes of grid cells in the entorhinal cortex 63 , further suggesting that MS activity is not directly involved in spatial codes within the hippocampal formation. Together with our results, this indicates that temporal codes could either be the result of MS-dependent computations within the entorhinal cortex 63 (1) or be generated intrinsically within the hippocampus itself (2).…”
Section: Discussionmentioning
confidence: 96%
“…While it was reported that time (but not place) cells could depend directly on medial entorhinal cortex (MEC) inputs 61 , other studies show that MEC lesions do not lead to any alterations in hippocampal time cell physiology 62 . Notably, a more recent investigation found that optogenetic pacing of the MS did not disrupt the spatial codes of grid cells in the entorhinal cortex 63 , further suggesting that MS activity is not directly involved in spatial codes within the hippocampal formation. Together with our results, this indicates that temporal codes could either be the result of MS-dependent computations within the entorhinal cortex 63 (1), or be generated intrinsically within the hippocampus itself (2).…”
Section: Discussionmentioning
confidence: 96%